DIGITAL TECHNOLOGIES AND THE FORMATION OF ELECTRONIC COMMERCE IN THE GLOBAL TOURISM INDUSTRY - Yuldashev Kamol Sharifovich,; Davronov Istamkhuja Olimovich, (TADQIQOTLAR, 2026)
Abstract. The emergence of electronic commerce became one of the defining processes in the modern transformation of the tourism industry. Between the end of the 1980s  and  the  year  2000,  the  appearance  of  the  World  Wide  Web  and  the  rapid development of internet technologies gave rise to a new digital infrastructure of tourism services,  within  which  online  reservation  systems,  online  travel  agencies,  search engines, price comparison services, and review platforms were successively formed. These  innovations  reduced  the  intermediary  role  of  traditional  travel  agencies  and shifted the booking of accommodation, of air tickets, and of tour packages into a direct online  format.  The  present  article  examines,  on  the  basis  of  a  historical  and chronological analysis, the key milestones in the formation of electronic commerce in tourism during this period, and it systematizes the main types of digital platforms that established the foundations of the contemporary online tourism market.